Наслідки Алжирської війни для Корсики: «чорноногі» та корсизм - Сипко, Богдана; Sypko, Bogdana (My University, 2015)
У статті на основі соціологічних опитувань, французької преси та сучасних французькомовних досліджень проаналізовано вплив репатріації «чорноногих» (європейських колоністів Алжиру) на піднесення корсиканського автономістського руху. Основний акцент зроблено на розгляді громадської думки корсиканців про «чорноногих».. On the basis of opinion polls, press and recent French studies the author analyzed the impact of repatriation of «pieds noirs» (European colonists of Algeria) on the rise of Corsican nationalism (corsisme). It was found that the main reasons for rejection of «pieds noirs» in Corsica are the following: government programs to support repatriated, which objectively did not apply to other Corsicans,the concentration by new arrivals of large plots of land and new ways of farming that contributed to immigration of workers from Northern Africa.
Consequences of Algerian War for Corsica: «Pieds noirs» and Corsisme
Keywords: Корсика; «чорноногі»; Алжирська війна; корсизм; націоналізм; Corsica; «pieds noirs»; Algerian War; corsisme; nationalism